The role of the fourth industrial revolution in accessible tourism: study and conceptualization of a web application - Teixeira, Pedro Miguel Beleza (2019)
The world is experiencing the beginning of the fourth Industrial Revolution, responsible for implementing a new digitalization era. This revolution originated in manufacturing, with industry 4.0 bringing a new reality to organizations. However, the scope of this new technological revolution is vast, and other sectors can benefit from the new digital era. In the Services Industry, tourism is an example of that, as Tourism 4.0 is the result of the impact of the fourth industrial revolution in this sector. Tourism 4.0 is the result of the impact of the fourth industrial revolution in tourism. An interesting challenge that this technological era brings to tourism is the social inclusion of people with disabilities. The accessible tourism market reveals huge potential, but despite this, this market is still largely ignored. Several technologies that promoted the fourth industrial revolution present capabilities to promote accessible tourism by improving tourism’s access conditions to people with disabilities. The present work developed a study in accessible tourism, understanding the main requirements for this market, and conceptualizing a Web application, for promoting accessibility in tourism. This Web application work as a mediator between the principal stakeholders. To gather requirements for the system, a triangulation matrix was elaborated using three methodological approaches: i) Literature Review; ii) website accessibility analysis of hotels located in the central region of Portugal; and iii) content analysis of some concurrent platforms. The requirements triangulation matrix allowed the identification of what requirements are crucial for the system success, which were used to conceptualize the solution with UML notation. This work intends to demonstrate the technological impacts of the fourth industrial revolution on society, especially on the promotion of a more accessible tourism